Türk Patent Hukukunda Çalışanların Buluşları - Öz, Turgut (Seçkin Yayıncılık, 2016)
Türk Hukukunda çalışanların buluşları hakkında mevcut düzenleme, patent haklarına ilişkin 24.6.1995 tarihli Kararnamede yer almaktadır. TBK m.427 hükmünde hizmet buluşları üzerinde işçi ve işverenin haklarının özel bir kanunla düzenleneceği belirtilmişse de, henüz böyle bir kanun yasalaşmamıştır. Değindiğimiz Kararnameye göre, çalışanların buluşları “hizmet buluşları” ve “serbest buluşlar” olmak üzere iki kategoriye ayrılmıştır. Kural olarak sadece hizmet buluşları bakımından işverene haklar tanınmıştır. İşveren, bedeli karşılığı buluşa ilişkin patent hakkını satın alma hakkına sahiptir. Serbest buluş bakımından ise, işverene sadece özel bazı şartlara bağlı olarak bazı öncelikler tanınmıştır.

Current regulation about inventions of employees in Turkish Law is included in a decree for patent rights, dated 6.24.1995. Even though Article 427 of TCO numbered 6098 stipulated that the rights of employer and employee on service inventions will be drawn up in a special law, such a regulation has not been made yet. According to the related decree, inventions of employees are divided into two categories as “service inventions” and “free inventions”. As a principle, only the rights on service inventions are granted to the employer. Employer has the right to buy the patent right of the invention in return for payment. In terms of free inventions, only some priorities are granted to the employer, depending on the specific conditions.
Inventions of Employees in Turkish Patent Law
Keywords: Buluş; Çalışanın buluşu; Hizmet buluşu; Serbest buluş; Patent kararnamesi; Invention; Invention of Employee; Service Invention; Free Invention; Patent Decree